Design and Development of Polyherbal Gel for Antifungal Activity - Sakshi Pramod Dalvi,; Pratiksha Prathamesh Nikam,; Madan Dadaso Pomaje, (The Bioscan, 2025)
The study reveals that a polyherbal antifungal gel combining Cassia tora leaf extract, Azadirachta indica leaf extract, Ficus benghalensis extract, and Hinokitiol is effective in tropical climates. The formulation is prepared using polyherb-loaded nanostructured lipid carriers (NLC) and is characterized by particle size, polydispersibility index, zeta potential, and physicochemical parameters.